1983
DOI: 10.1037/0022-3514.45.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept: The construct validity of interpretations based upon the SDQ.

Abstract: The Self-Description Questionnaire (SDQ) is a multidimensional instrument designed to measure seven facets of self-concept hypothesized in Shavelson's hierarchical model. The SDQ, along with measures of attributions and academic achievement, was administered to primary school students from two quite diverse populations. Separate factor analyses of responses from the two groups were similar and clearly demonstrated the seven factors that the SDQ is designed to measure. The small correlations among the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
12

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 28 publications
5
128
0
12
Order By: Relevance
“…A large amount of method variance remains undefined, necessitating further correlational research (see Marsh et al, 1983 for an excellent illustration), as well as the type of logical and experimental work outlined by Shavelson et al (1976). We must also keep in mind that self-esteem measures fail to tap many other dimensions of self-conception and that every measurement approach must be evaluated in terms of the particular aspect of self it purports to capture (Gordon, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of method variance remains undefined, necessitating further correlational research (see Marsh et al, 1983 for an excellent illustration), as well as the type of logical and experimental work outlined by Shavelson et al (1976). We must also keep in mind that self-esteem measures fail to tap many other dimensions of self-conception and that every measurement approach must be evaluated in terms of the particular aspect of self it purports to capture (Gordon, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Self Description Questionnaire II (SDQ2); (Marsh, Relich, & Smith, 1983-Versão portuguesa: Fontaine, 1991a): avalia o auto-conceito em adolescentes dos 12 aos 18 anos. Compõem-se por 102 itens, repartidos em 11 subescalas, das quais três se relacionam com parâmetros do auto-conceito referente ao domínio escolar.…”
Section: Auto-avaliação Dos Factores De Risco Do Aluno (Afra) -Desenvunclassified
“…For instance, Marsh, Kong, and Hau (2001) reported that their participants' English selfesteem was positively affected by their English achievement. On the other hand, Marsh, Relich, and Smith (1983) in their research found that the learners' school performance was highly affected by their academic self-esteem. Thus, it seems evident that there is a significant association between these two variables.…”
Section: Statement Of the Problemmentioning
confidence: 99%